Hybrid Knowledge-Based System for Collaborative Green Automotive Manufacturing Management - N. M. Zuki, N. M.; Mohd Kamal, Mohd Nawawi; Adam Shariff Adli, Aminuddin (Trans Tech Publications, Switzerland, 2015)
The objective of this research paper is to demonstrate the application of hybrid knowledge-based system, gauging absences of pre-requisites (GAP), and analytic hierarchy process (AHP) approaches for selecting the improvement programs for Collaborative Green Manufacturing Management (CGMM) system. In this research, a generic knowledge-based system is developed to measure the level of CGMM adoption in automotive manufacturers compared to the ideal system. Using the GAP and AHP tools, the key green manufacturing improvement programs can be prioritized and demonstrated with an illustrative example.